2016
DOI: 10.15275/rusomj.2016.0406
|View full text |Cite
|
Sign up to set email alerts
|

Influence of selenium on clinical and laboratory parameters in patients with rheumatoid arthritis and subclinical hypothyroid dysfunction

Abstract: Abstract:The article presents data on the effectiveness of the impact of selenium on clinical and laboratory parameters of rheumatoid arthritis (RA) in patients with subclinical hypothyroid dysfunction (SHTD). Aim -to study the influence of selenium on the clinical and laboratory parameters in patients with RA and SHTD. Material and Methods -The study included 78 patients with RA and SHTD. All patients underwent a complete clinical and functional, instrumental and laboratory examination for RA and thyroid dysf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…One report revealed that Se supplementation has an antioxidant effect as it upregulates selenoproteins and downregulates inflammation in autoimmune disorders [ 43 ]. The significance of Se supplementation, however, is still not distinct for the treatment of RA patients based on confusing data [ 44 , 45 ]. Moreover, the associated toxic effect of Se for the treatment of arthritis as an antioxidant supplement is debatable [ 46 ].…”
Section: Serum Selenium Status In Rheumatoid Arthritismentioning
confidence: 99%
“…One report revealed that Se supplementation has an antioxidant effect as it upregulates selenoproteins and downregulates inflammation in autoimmune disorders [ 43 ]. The significance of Se supplementation, however, is still not distinct for the treatment of RA patients based on confusing data [ 44 , 45 ]. Moreover, the associated toxic effect of Se for the treatment of arthritis as an antioxidant supplement is debatable [ 46 ].…”
Section: Serum Selenium Status In Rheumatoid Arthritismentioning
confidence: 99%
“…Clinical and experimental studies have shown that in pathogenesis of diseases such as cataracts and pancreatic cystic fibrosis is a scarce of a number of elements including selenium (Kumara & Priyadarsinib, 2014). It is not possible to say that selenium scarce is cause of chronic hepatitis or rheumatoid arthritis, but the severity of these diseases depends on element concentration in the body (Knyazeva et. al., 2016;Galal et.…”
Section: Ukrainian Journal Of Ecology 10(4) 2020mentioning
confidence: 99%